2019
DOI: 10.31011/reaid-2019-v.87-n.25-art.202
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos diagnósticos e psicotrópicos das pessoas privadas de liberdade

Abstract: Objetiva-se caracterizar o diagnóstico de saúde mental das pessoas privadas de liberdade e os principais psicotrópicosque fazem uso. Apresenta-se sob a forma de um estudo descritivo e quantitativo fundamentado no tipo documental realizado no Complexo Penal Estadual de Mossoró/RN. Foram utilizados 125 prontuários: 57 de homens e 68 de mulheres.Os prontuários estavam inseridos no período de 2010 a 2017. Os dados foram tabulados em planilha eletrônica e transferidos para o programa estatístico Statistical Package… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…In line with the study, Feitosa (2019) reports that around 38.6% of those deprived of their liberty use controlled medications for a period equal to or less than 12 months. Also, it reports that there is a growing increase in this number, as some professionals who work in prison are based on the belief "medicated subjects, silent jail" (FEITOSA et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the study, Feitosa (2019) reports that around 38.6% of those deprived of their liberty use controlled medications for a period equal to or less than 12 months. Also, it reports that there is a growing increase in this number, as some professionals who work in prison are based on the belief "medicated subjects, silent jail" (FEITOSA et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of psychotropic drugs, a study conducted by Feitosa et al 20 revealed a high prevalence of incarcerated women using these medications. It was also noted that diagnoses of psychiatric disorders were frequently associated with conditions arising from imprisonment, such as anxiety, sadness, fear, distress, and boredom.…”
Section: Discussionmentioning
confidence: 99%

The use of medications by incarcerated women: an exploratory study

Aparecida de Lima Ribeiro,
Guedes Morais Gonzaga de Souza,
Lulio
et al. 2024
HSJ
“…Ademais, percebe-se um número pertinente e crescente de doenças psíquicas em todo o globo, realidade também observada em prisões e centros de segurança. De acordo com Feitosa et al (2019), a respeito da condução da saúde mental dentro de presídios, pode-se perceber um elevado número de indivíduos que fazem uso de psicofármacos -como medicamentos para dormir ou tranquilizantessem um diagnóstico elucidado.…”
Section: Saúde Mental Da Pessoa Privada De Liberdade: Agravos (In)vis...unclassified